Genetic Characterization of Multiple Components Contributing to Fusarium Head Blight Resistance of FL62R1, a Canadian Bread Wheat Developed Using Systemic Breeding - Zhang, Wentao; Boyle, Kerry; Brûlé-Babel, Anita L.; Fedak, George; Gao, Peng; Robleh Djama, Zeinab; Polley, Brittany; Cuthbert, Richard D.; Randhawa, Harpinder S.; Jiang, Fengying; Eudes, François; Fobert, Pierre R. (Frontiers in Plant Science, 2020)
Fusarium head blight (FHB) is a devastating fungal disease of small-grain cereals that results in severe yield and quality losses. FHB resistance is controlled by resistance components including incidence, field severity, index, Fusarium Damaged Kernels (FDKs), and the accumulation of the mycotoxin DON. Resistance conferred by each of these components is partial, and must be combined to achieve resistance sufficient to protect wheat from yield losses. In this study, two biparental mapping populations were analyzed in Canadian FHB nurseries and QTL mapped for the traits listed above. Nine genomic loci, on 2AS, 2BS, 3BS, 4AS, 4AL, 4BS, 5AS, 5AL and 5BL, were enriched for the majority of the QTL controlling FHB resistance. The previously validated FHB resistance QTL on 3BS and 5AS, affected resistance to severity, FDK and DON in these populations. The remaining seven genomic loci co-localize with flowering time and/or plant height QTL. The QTL on 4B was a major contributor to all field resistance traits and plant height in the field. QTL on 4AL showed contrasting effects for FHB resistance between Eastern and Western Canada, indicating a local adapted resistance to FHB. Results presented here provide insight into the genetic architecture underlying these resistant components and insight into how FHB resistance in wheat is controlled by a complex network of interactions between genes controlling flowering time, plant height, local adaption and FHB resistance components.